2023
DOI: 10.7454/jki.v26i1.1947
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of Adolescents Experiencing Online Game Addiction During the COVID-19 Pandemic

Yanuar Fahrizal,
Hafizuddin Slamet Irmawan

Abstract: The availability of the internet and the increase in stress in adolescents caused by the pandemic have led adolescents to frequently seek entertainment through online games. Online gaming can negatively impact adolescents by causing a decline in their physical health, psychological issues, difficulty forming healthy social relationships, and decline their quality of life. This study identified the relationship between online game addiction and the quality of life of adolescents during the COVID-19 pandemic. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Students can learn while playing with their peers. A study demonstrated that learning that involves cooperation and solving cases increases learning motivation with feelings of satisfaction and pride in oneself (Afifah & Syahreni, 2005;Fahrizal & Irmawan, 2023). In addition, students can learn in a gaming atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Students can learn while playing with their peers. A study demonstrated that learning that involves cooperation and solving cases increases learning motivation with feelings of satisfaction and pride in oneself (Afifah & Syahreni, 2005;Fahrizal & Irmawan, 2023). In addition, students can learn in a gaming atmosphere.…”
Section: Introductionmentioning
confidence: 99%